Peningkatan Keterampilan berpikir Kritis Siswa dengan menggunakan model inkuiri terbimbing bervisi SETS - neti afrianis (Konfigurasi : Jurnal Pendidikan Kimia dan Terapan, 2017)
The process of teaching and learning in the schools only emphasized on the knowledge and understanding aspects and lack develop the skill of critical thinking of students so that they are poorly trained to develop reasoning power in responding and solving problem or applied the concept of science in life. The objective of this study was to improve the critical thinking skill of student using guided inquiry model with SETS (Science, Environment, Technology and Social) vision. This research was conducted in Senior High School (SMAN) 1 Kampar, class of XI IPA-1 and XI IPA-3. Improvement of critical thinking skill of student is measured using pre-test and post-test. The score of pre-test and post-test was analyzed using the N-Gain tested. The result of this study showed that skill to basic explanation, constructing of basic practice, generalization, and hypothesis making as the indicator of thinking ability of student were catagorized as moderate, meanwhile indicator of applied the concept was high with 0.834 of N-Gain value. The critical thinking of students for each indicator were increased that reflected from average value of pre-test and post-test of students. The finding of this study was  guided inquiry model with SETS vision able to improve the critical thinking of student of SMAN 1 Kampar.